Deep structures underneath the Sihong Segment of the Tan-Lu Fault Zone, Eastern China: Interpretations of gravity anomaly and seismic profiles. (1st June 2019) - Li, Changbo; Jiang, Ren; Zeng, Jianwei; Yu, Junjie; Liu, Kai; Peng, Bo; Lao, Jinxiu; Zhao, Ling
Graphical abstract: Highlights: The Xinyi-Xindian fault (F2) and Qiaobeizhen-Suqian fault (F5) are segmented.. The bedrock surface shows a tectonic structure of two grabens and one horst. The Moho discontinuity depth underneath the Sihong area shows an obvious uplift. A fault-depression superimposed basin developed in the study area.. Abstract: The Sihong Segment of the Tan-Lu Fault Zone (SSTLFZ) is located in the Sihong county of the Jiangsu province and composed of 5 branches, which are mainly buried faults. The Tan-Lu Fault Zone is characterized by segmentation and its regional distribution, deep structures and geodynamic evolution in the Sihong area remains controversial. We provided evidence of gravity anomaly and seismic reflection profiles suggesting that the Xinyi-Xindian fault (F2) and Qiaobeizhen-Suqian fault (F5) of the SSTLFZ are segmented, which appear as thrust faults in the north and normal faults in the south. The F2, F5 and Mohe-Lingcheng fault (F3) are inferred as Quaternary faults. Based on the inversion of gravity anomaly, the tectonic structure of the bedrock consists of two grabens and one horst and the Moho discontinuity depth in the Sihong area shows an obvious uplift. We conclude that a fault-depression superimposed basin developed inner the SSTLFZ. The northern segments of the F2 and F5 were inverted due to the continuous compression since Quaternary.